A Sampling of Sleep Apps and Their Benefits. Issue 1 (2nd January 2023) - Becker, Danielle A.
Abstract: Librarians, clinicians, and library patrons would benefit from exploring the potential of applying mobile technology to help improve their overall health and wellness. One of the most common problems experienced by many children, adolescents, and adults is sleeplessness, poor sleep quality, and inadequate sleep hygiene. A popular and emerging trend in mobile technology is the development of sleep improvement and tracking apps. These apps have infiltrated the market, making it difficult for users to discern which apps will appeal to them without downloading and testing each of them. This article aims to introduce users to 10 popular sleeping apps and their benefits.